ChemInform Abstract: Rhodium(III)‐Catalyzed Oxidative Alkenylation of 1, 3‐Dithiane‐Protected Arenecarbaldehydes via Regioselective C—H Bond Cleavage. Issue 26 (June 2015) - Unoh, Yuto; Hirano, Koji; Satoh, Tetsuya; Miura, Masahiro
Abstract The 1, 3‐dithiane group serves as an effective directing group to allow the ortho‐selective monoalkylation.